Association between lipid indices and 10-year cardiovascular risk of a cohort of black Africans living with type 2 diabetes mellitus - Azeez, Taoreed Adegoke (Journal of Advances in Internal Medicine, 2021)
Introduction Diabetes mellitus is an established cardiovascular risk factor. Diabetes mellitus impairs lipid metabolism and enhances atherosclerosis development. Absolute lipid parameter are inadequate in predicting cardiovascular risk and some lipid indices have been reported to circumvent this deficiency. The objective of the study was to determine the association between these lipid indices and 10-year cardiovascular risk among black Africans with diabetes.Methods Seventy individuals (35 males and 35 females) living with diabetes who attended the diabetes clinic of a referral hospital in South-western Nigeria were recruited to the study. Ethical approval and participants’ informed consent were duly obtained. Fasting plasma glucose, fasting lipid profile and glycated haemoglobin were done using appropriate laboratory techniques. Atherogenic index of plasma, atherogenic coefficient, Castelli’s risk index I, Castelli’s risk index II and CHOLindex were calculated using appropriate formulae. QRISK 3 score was obtained using a validated calculator. The association between QRISK 3 and the lipid indices was determined using Pearson’s correlation.Results The mean age of the participants was 53.34 ± 9.57 years. The mean duration of diabetes mellitus among the participants was 6.29 ± 2.78 years. The mean HbA1c and FPG were 6.98±0.72% and 6.32±0.87 mmol/L respectively. The mean QRISK 3 score was 7.58±4.80. There was a statistically significant and positive correlation between QRISK 3 score and AIP, AC, CR I and CR II. CHOLindex did not significantly correlate with QRISK 3 score.Conclusion Among black Africans with diabetes, lipid indices (AIP, AC, CR I and CR II) significantly correlated with QRISK 3 score and therefore may be used as cheap markers of 10-year cardiovascular risk in these individuals.